Modelo de gestión para el mejoramiento de la administración integral de documentos y archivos en el gobierno autónomo descentralizado del distrito metropolitano de Quito, 2024 - Caleño Quinte, Mary Elizabeth (2025)
This integration Project collects, diagnoses, analyzes, and defines the Management Model for the improvement of the comprehensive administration of documents, archives, applicable to the Decentralized Autonomous Government of the Metropolitan District of Quito (hereinafter referred to as GADDMQ) 2024, within the framework of the e-government, transparency, and access to the public information by breaking down and articulating their main components, processes, and technical and technological resources for the exercise of institutional documents and archival management which leads to several improvements through the application of the model in the municipal departments strengthen the normalization, standardization, and articulation of the archives which are part of the Metropolitan System of Document and Archive Management of the GADDMQ. The structure of the integration project starts with the collection of theoretical, scientific information and updated regulations that support the variables of the research through bibliographic sources such as books, scientific articles, national and institutional regulations magazines, among others. Additionally, it addresses the qualitative and quantitative analysis of the situation of document and archive management in the GADDMQ, in relation to these factors: administrative, regulatory, procedural, services and application of technologies, information which allowed to propose the Management Model for improving the whole administration of documents and archives which consider viable and necessary alternatives to solve the identified problem which involves the following components: strategic, archives administration, document management processes, technological, and cultural.